Survey Of The Level Of Upper Passing Skills In Extracurricular Volleyball Students At The Agribusiness Vocational High School In The City Of Bengkulu - Risdiawan, Pigi; Sumantri, Ajis; Elra Perdima, Feby (Sinar Sport Journal, 2023)
This study aims to determine the purpose of this study is to determine the level of Upper Passing skills in bolavoli game of extracurricular bolavoli students at SMK Agribisnis Bengkulu City. This research is Quantitative research using survey methods with test techniques, The population in this study were 17 students of SMK Agribisnis Bengkulu City. To get a sample in this study conducted by purposive sampling technique. Based on the results of research and discussion of Bengkulu City Agribusiness Vocational High School, the category is GOOD. This is because male volleyball extracurricular participants are not all proficient in playing volleyball. There are several participants who are beginners, and there are also children who have abilities in other sports, so that the volleyball top passing ability possessed by 6 people or (35.329%) is at a score of> 56, 11 people or (64.70%) are at a score of 43-55, 0 people or (0%) are at a score of 31-41, 0 people or (0%) are at a score of 20-30, 0 people or (0%) are at a score of <19.